UPAYA PENINGKATAN PELAYANAN PUBLIK PRIMA DI KEJAKSAAN NEGERI SLEMAN - Gina Nur Aulia; Beni Hidayat (LPPM Universitas Ekasakti Padang, 2023)
The purpose of this study is to find out the efforts made by the Government towards the quality of public services, namely the provision of services for the community by the government to fulfill the initial needs of the community by creating community welfare, public services must guarantee the welfare of people's lives evenly. The community considers that public service is a human right because it has human rights that have been inherent in human beings since birth. Public service regulations in Indonesia have been regulated in Law Number 25 of 2009 which regulates public services. In Law Number 25 of 2009 Article 1 explains that service standards Public service at the Attorney General's Office of the Republic of Indonesia includes the scope of services and administration. Public services must be integrated with public information services aimed at providing transparent information to the public. Regulations for the quality of public services have been regulated in the attorney general's office itself, namely in the Regulation of the Attorney General of the Republic of Indonesia Number: PER-011/A/JA/06/2013 concerning Public Service Standards for the Attorney General's Office of the Republic of Indonesia, Article 1 explains that Public Service Standards at the Attorney General's Office of the Republic of Indonesia include scope of services and administrative services. Service and administrative services must be integrated with public information services which aim to provide information in a flexible and transparent manner to the public.